การปรับตัวของสื่อพื้นบ้านโนราในสังคมไทย - นิธิมา ชูเมือง (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This research aims at studying the causes of recent adaptation of "Nora" traditional media, studying the recent adaptation of "Nora" traditional media in terms of form and content, and studying the results of the adaptation. It is a qualitative research employing in-depth interviews with 9 "Nora" masters, 9 "Nora" performaners, 3 local scholars, who live in the area of Nakorn Srithammarat, Songkhla, and Pattalung provinces. In addition, both participant observation and non-participant observation were used. It is found that there are two types of "Nora" performance, to wit "Nora Rong Khru" (Performing "Nora" for doing ritual) and "Nora Sadaeng" (Performing "Nora" for entertaining). "Nora Sadang" is an adapted "Nora" performance in contemporary Thai society. There are three sub-categories of this performance, namely "Nora Boran" (Ancient/Classical Nora), "Nora Samai Mai" (Modern Nora), and "Nora Prayuk" (Applied Nora). Three causes of the recent adaptation of "Nora" traditional performance include the coming of new media, audience s favor, and income. The recent adaptation of Nora traditional media is an emergent culture combining between the residual "Nora" performance and dominant cultures that are modern drama and "Luk Thung" (country music) musical performance. In term of the form adaptation, the adaptation includes the truncation and reduction of the traditional elements of Nora performance and the substitution and addition of mainstream cultural elements. In terms of the content adaptation, the original contents in the part of poems are truncated and substituted by contents of current situations. Regarding the contents in the play part, there are substitution of modern drama content and revival of traditional performing content. Additionally, it is revealed that "Nora" traditional media currently functions in educating, informing, entertaining, and social criticizing. There are four consequences of the recent adaptation of "Nora" traditional media. Firstly, each subtype of "Nora Sadaeng" has different target groups, different interrelation between the performers and the audience, different profound degree of education and different value in "Nora" dramatic arts. The findings also indicate that in the current adaptation of the three types of "Nora Sadaeng", the main elements of Nora performance such as singing, dancing, and "Tambot" (the improvised dance from poems interpreting) are still preserved. These are significant and unique elements of Nora performance as well as the communication via the performance. In addition, the basic factors of the survival of the current "Nora" traditional media in Thai society include beliefs about Nora masters and beliefs about rituals in "Nora Rong Khru" These beliefs function as keys for the preservation of "Nora" performance for new generations.